Efficacy and safety of intra-articular therapies in rheumatic and musculoskeletal diseases: an overview of systematic reviews. Issue 2 (8th June 2021) - Rodriguez-García, Sebastián Cruz; Castellanos-Moreira, Raul; Uson, Jacqueline; Naredo, Esperanza; O'Neill, Terence W; Doherty, Michael; Boesen, Mikael; Pandit, Hemant; Möller Parera, Ingrid; Vardanyan, Valentina; Terslev, Lene; Kampen, Will Uwe; et al.
Abstract : Objective: To summarise the evidence on intra-articular therapies (IAT) to inform the 2020 EULAR recommendations. Methods: An overview of systematic reviews (SR) including randomised-controlled trials (RCTs) of IAT in adults with arthropathies was performed up to July 2020. Pain, function, and frequency of adverse events were the main efficacy and safety outcomes, respectively. Quality was assessed with the A MeaSurement Tool to Assess Systematic Reviews (AMSTAR)-2 tool. Results: Of 184 references identified, 16 met the inclusion criteria, and a search of their reference lists identified 16 additional SRs. After quality assessment, 29 were finally included. Of these, 18 focused on knee osteoarthritis (KOA), 6 on hip osteoarthritis (HOA), 3 on shoulder capsulitis (SC), and 3 on rheumatoid arthritis. Overall, hyaluronic acid showed a small effect on pain and function in KOA but not in HOA or shoulder capsulitis. Intra-articular glucocorticoids showed a small effect in pain and function in KOA and function in HOA and SC. Platelet-rich plasma showed benefit in pain and function in KOA but not in HOA. Mesenchymal stem cells behaved similarly. Most SR results were of moderate quality and RCTs included often presented a high risk of bias, mainly due to inadequate blinding and heterogeneous results. All interventions were well tolerated with no clear safety differences. Conclusions: This overview underlines that most IAT currently used in KOA, HOA, and SC exert small effects and are well tolerated. However, no firm conclusions can be drawn for inflammatory arthritis due to the limited data found.